The culture of patriarchy, gender bias, and class discrimination in Mahesh Dattani’s Tara - Kumar, Tribhuwan (Linguistics and Culture Review, 2021)
This research paper, which makes use of Mahesh Dattani's play Tara (1990), emphasises the concept of social issues such as gender inequalities, suffering, and depression, which are experienced by both men and women in equal measure. Gender discrimination, injustice done solely on the basis of gender, and preference for male children in Indian homes are all issues that are the focus of this research. Tara, Dattani's other play, addresses the issue of gender discrimination. The play addresses the emotional and physical separation of conjoined twins. It exemplifies the society's ingrained patriarchal system. Women act as a key in patriarchy's hands, ensuring the survival of patriarchal values. The purpose of this article is to discuss and analyse the play's issue of female marginalisation. Chandan, a boy child, is preferred to Tara, a girl child, in an Indian family. Despite the fact that she is Tara's mother, Bharati wrecks her daughter's life and ultimately suffers as a result of her harsh behaviour. Dr. Thakkar makes an error in his capacity as a scientist and a technophile. Bharati and her father bribed him with a piece of land in exchange for Tara’s death.